2004
DOI: 10.1080/13577140410001679202
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Outcome of Conventional Osteosarcoma at Two Specialist International Orthopaedic Oncology Centres

Abstract: Objective: To determine the prognostic value of patient and treatment parameters in osteosarcoma, and whether these are equally important across international boundaries. Design: Retrospective, cross-sectional study of 428 patients diagnosed with around-knee osteosarcoma, between 1990 and 1997 in Birmingham, UK, and Bologna, Italy. Disease-free survival (DFS) and overall survival (OS) assessed by KaplanMeier, Fisher's PLSD and Cox proportional hazard regression. Results: Five-year DFS and OS were 56 and 73% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Other studies have also found no association between surgical margins and overall survival. Ford et al [5] looked at a total of 428 patients across two large orthopaedic oncology centers and found that adequacy of surgical margins was not associated with overall survival. However, margins were graded qualitatively (intralesional, marginal, wide, and radical) versus quantitatively and the length of followup was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found no association between surgical margins and overall survival. Ford et al [5] looked at a total of 428 patients across two large orthopaedic oncology centers and found that adequacy of surgical margins was not associated with overall survival. However, margins were graded qualitatively (intralesional, marginal, wide, and radical) versus quantitatively and the length of followup was not recorded.…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic residual tumour independently increased risk of death in another study including 1,702 cases of osteosarcomas [20]. But one study [21] found that adequacy of surgical margins was not significantly associated with DFS or OS. Our result also showed no significant correlation between margin status and OS using Kaplan-Meier method.…”
Section: Discussionmentioning
confidence: 99%
“…There is still controversy on the correlation of surgical margins and survival of osteosarcoma in different studies [3,20,21]. Inadequate margins (including intralesional margin and marginal margin based on Enneking's classification [10]) were found to be associated with poor event-free survival in a study including 789 patients with extremity osteosarcomas [3].…”
Section: Discussionmentioning
confidence: 99%
“…A concordance to the secondary lesions was also seen in the tumour response to the chemotherapy (good/good in the girl; regression grade I according to Salzer/Kuntschnik and poor/poor in the boy; regression grade IV according to Salzer/Kuntschnik). Another possible prognostic factor in the disease is the elevation of alkaline phosphatase in the laboratory analysis at time of diagnosis [11]. In the first described case, no elevation was noticeable; in the second case an elevation above the norm was seen.…”
Section: Discussionmentioning
confidence: 97%